Analisis Karakteristik Volumetrik Campuran Laston Berdasarkan Dust Binder Ratio dan Ketebalan Film Aspal - Yuniarti, Ratna; Widianty, Desi; Rohani, Rohani; Hasyim, Hasyim; Mahendra, Made (LPPM Universitas Mataram, 2024)
fine particles and asphalt in asphalt concrete. The dust binder ratio also influences the asphalt film thickness, which plays an important role in increasing the resistance of asphalt mixture to humidity and temperature. The aim of this study was to analyze the effects of the dust binder ratio and asphalt film thickness on the volumetric properties of mixtures with various aggregate particle size distributions. Based on the analysis results, it was concluded that the dust binder ratio is inversely proportional to the thickness of the asphalt film. The dust binder ratio and asphalt film thickness had a significant effect on the volumetric properties of the mixture. The greater the value of the dust binder ratio, the more voids in the mixture, whereas the voids in the mineral aggregates and the voids filled with bitumen decreased. The thicker the asphalt film, the fewer the voids in the mix, and the voids in the mineral aggregates and those filled with bitumen increased. In this study, the volumetric properties of the mixture that met the Bina Marga specifications were obtained through the use of filler and asphalt with a dust binder ratio value between 1.2-1.32.